Serum total Calcium level in patients with Thalassemia - Sanjyoti Bandebuche; Vijaykumar Sagar; Alka Sontekke (International Journal of Medical Research and Review, 2013)
Introduction: Thalassemia is a genetic disorder characterized by the complete absence or reduced synthesis of α or β globin chains. The mainstay of treatment of severe β thalassemia is regular blood transfusion. Repeated blood transfusion results in hypoparathyroidism and in turn hypocalcemia due to iron overload. The aim of the study was to evaluate calcium status in thalassemia patients by estimating and comparison of serum total calcium and iron levels between normal and thalassemic patients.Methods: The study comprised of clinically diagnosed β thalassemia Major patients and age matched controls. Results: The results revealed stastically significant decrease in serum total calcium in thalassemia patients as compared to normal while serum iron levels found to be increased indicating iron toxicity.Discussion: On diagnosis as well as periodic assessment of thalassemia patients for hypocalcemia may be beneficial and if found calcium and vitamin D supplementation may be carried out in order to improve their bone health.